Antibody Fab‐Fc properties outperform titer in predictive models of SIV vaccine‐induced protection. Issue 5 (2nd May 2019) - Pittala, Srivamshi; Bagley, Kenneth; Schwartz, Jennifer A; Brown, Eric P; Weiner, Joshua A; Prado, Ilia J; Zhang, Wenlei; Xu, Rong; Ota‐Setlik, Ayuko; Pal, Ranajit; Shen, Xiaoying; Beck, Charles; et al.
Abstract: Characterizing the antigen‐binding and innate immune‐recruiting properties of the humoral response offers the chance to obtain deeper insights into mechanisms of protection than revealed by measuring only overall antibody titer. Here, a high‐throughput, multiplexed Fab‐Fc Array was employed to profile rhesus macaques vaccinated with a gp120‐CD4 fusion protein in combination with different genetically encoded adjuvants, and subsequently subjected to multiple heterologous simian immunodeficiency virus (SIV) challenges. Systems analyses modeling protection and adjuvant differences using Fab‐Fc Array measurements revealed a set of correlates yielding strong and robust predictive performance, while models based on measurements of response magnitude alone exhibited significantly inferior performance. At the same time, rendering Fab‐Fc measurements mathematically independent of titer had relatively little impact on predictive performance. Similar analyses for a distinct SIV vaccine study also showed that Fab‐Fc measurements performed significantly better than titer. These results suggest that predictive modeling with measurements of antibody properties can provide detailed correlates with robust predictive power, suggest directions for vaccine improvement, and potentially enable discovery of mechanistic associations. Synopsis: Fab‐Fc array measurements are used to analyse humoral responses to vaccination. Accounting for antibody qualities and not just the overall response magnitude allows predictive modeling of protection in two different simian immunodeficiency virus (SIV) vaccine studies. A high‐throughput, multiplexed Fab‐Fc array is used to profile humoral responses to vaccination in an SIV challenge study, revealing antibody properties associated with protection. The magnitude of the antibody response is weakly correlated with protection and does not support predictive modeling. Models employing antibody Fab:Fc properties can accurately and robustly predict risk of infection in cross‐validation evaluation. Similarly, models incorporating antibody properties are more accurate and robust in classifying vaccine group than those trained with response magnitude alone. Abstract : Fab‐Fc array measurements are used to analyse humoral responses to vaccination. Accounting for antibody qualities and not just the overall response magnitude allows predictive modeling of protection in two different simian immunodeficiency virus (SIV) vaccine studies.